2021
DOI: 10.1007/s10853-021-05799-0
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial structures between aluminum nitride and Cu–P–Sn–Ni brazing alloy with Ti film

Abstract: Control of Ag electro chemical migration is crucial for long-term reliability of electrical components in high-voltage applications. In this work, Cu was bonded onto an AlN substrate at temperatures between 650 °C and 950 °C for 1 h using a Ag Free Cu-P-Sn-Ni brazing filler metal with Ti as an active metal addition. The interfacial structure between the Cu and the AlN and the mechanical properties of the bond were both investigated. Three different phases which contain Ti and O were observed during the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…2 Liao et al 3 used a W-Cu composite with a lower coefficient of thermal expansion (CTE) instead of pure Cu to form the joint with AlN, which can prevent mechanical failures at the interface resulting from mismatched CTE between Cu and AlN. The maximum average tensile strength for the joints reached 26.76 MPa at 800 • C. Terasaki et al 4 utilized a kind of Ag-free Cu-P-Sn-Ni brazing alloy with Ti as an active metal addition to joining Cu and AlN. They found that Cu/AlN interfacial fracture was completely suppressed above 850 • C, where rutile was the dominant phase at the Cu/AlN interface.…”
Section: Coefficient Of Thermal Expansion (Cte)mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Liao et al 3 used a W-Cu composite with a lower coefficient of thermal expansion (CTE) instead of pure Cu to form the joint with AlN, which can prevent mechanical failures at the interface resulting from mismatched CTE between Cu and AlN. The maximum average tensile strength for the joints reached 26.76 MPa at 800 • C. Terasaki et al 4 utilized a kind of Ag-free Cu-P-Sn-Ni brazing alloy with Ti as an active metal addition to joining Cu and AlN. They found that Cu/AlN interfacial fracture was completely suppressed above 850 • C, where rutile was the dominant phase at the Cu/AlN interface.…”
Section: Coefficient Of Thermal Expansion (Cte)mentioning
confidence: 99%
“…The maximum average tensile strength for the joints reached 26.76 MPa at 800°C. Terasaki et al 4 . utilized a kind of Ag‐free Cu–P–Sn–Ni brazing alloy with Ti as an active metal addition to joining Cu and AlN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the melting temperature of Cu-P brazing filler metal is still too high to braze copper alloys with low melting points, such as brass. Therefore, several novel Cu-P brazing filler metals have been developed, such as Cu-P-Ni [5,6], Cu-P-Ag [7], Cu-P-Sn [8,9], Cu-P-Zr [10] and Cu-P-RE (rare earth) [11], some of which have been used in the manufacturing industry for brazing copper alloys.…”
Section: Introductionmentioning
confidence: 99%